GROWTH RESPONSE OF SUGARCANE BUD SET (Saccharum officinarum L)AT SEVERAL AGES OF PLANTING MATERIALS AND CONCENTRATIONS OF IBA - Jerry Afrimsa Sijabat (Agripreneur : Jurnal Pertanian Agribisnis, 2021)
The research purpose to decide the growth response bud set cane against IBA concentrations at some planting materials. Research conducted at the field of the Faculty of Agriculture USU, started from May to August used a factorial randomized block design with two factors ei ages of planting material(6,7,8 months) and concentration of growth regulators IBA (100,200,300 ppm). The parameters were the percentage of seedlings grow, the rate of germination, plant length, sum of leaf, diameter, total of tillers, total leaf area, root volume, root length and shoot dry weight. The results showed that the germination rate against age had significant effect by planting material and concentration of growth regulators. The interaction between the ages of planting materials and concentration of growth regulators had not significantly effect on all parameters.